A Comparison of Performance Between Straight-Line Muscle and Curved Muscle Models. (September 2017) - Hwang, Jaejin; Knapik, Gregory G.; Dufour, Jonathan S.; Marras, William S.
The straight-line muscle biomechanical models of the lumbar spine have been utilized to predict spinal loads to assess the potential risk of work-related injuries. The curved muscle paths have been suggested to realistically simulate muscles' behavior in complex lumbar motions. However, the effect of curved muscle paths on the modeling performances and spinal loads in the lumbar spine model during complex lifting exertions has not been fully investigated. The objective of this study was to characterize the differences in modeling performances and spinal loads between the conventional straight-line muscle model and the curved muscle model of the lumbar spine. Twelve subjects (6 males and 6 females) participated in this study. Mean values and standard deviations of age, body mass, and height of all subjects were 26.6 (5.3) years, 73.6 (13.3) kg, and 172.7 (5.4) cm, respectively. Electromyographic (EMG) activities with surface electrodes (Motion Lab Systems MA300-XVI, Baton Rouge, Louisiana, USA) were collected over 10 trunk muscles (pair of the latissimus dorsi, erector spinae, rectus abdominis, external oblique, and internal oblique) with 1000 Hz sampling rate. The OptiTrack optical motion capture system (NaturalPoint, Corvallis, OR, USA) with 24 Flex 3 infrared cameras was used to monitor whole body kinematics with 100 Hz sampling rate. A Bertec 4060A force plate (Bertec, Worthington, OH, USA) was used to measure ground reaction forces with 1000 Hz sampling rate. Customized Laboratory software via a National Instruments USB-6225 data acquisition board (National Instruments, Austin, TX, USA) was utilized to collect all signals simultaneously and efficiently run the model. Subjects performed complex lifting tasks by various load weight (9.1kg and 15.9kg), load origins (counterclockwise 90⁰, counterclockwise 45⁰, 0⁰, clockwise 45⁰, and clockwise 90⁰), and load height (mid-calf, mid-thigh, and shoulder). Both curved muscle model and straight-line muscle model were tested under same experiment conditions, respectively. The curved muscle model showed better model fidelity (average coefficient of determination (R2) = 0.83; average absolute error (AAE) = 14.4%) than the straight-line muscle model (R2 = 0.79; AAE = 20.7%), especially in upper levels of the lumbar spine. The curved muscle model showed higher R2 than the straight-line muscle model, and the T12/L1 level showed the biggest difference as 0.1. The curved muscle model had lower AAE than the straight-line muscle model, and the T12/L1 showed the biggest difference as 18%. The curved muscle model generally showed higher compression (up to 640N at T12/L1), lower anterior-posterior shear loads (up to 575N at T12/L1), and lower lateral shear loads (up to 521N at T12/L1) than the straight-line muscle model. The biggest difference in spinal loads between two models (especially in anterior-posterior shear and lateral shear loads) occurred at upper levels of the lumbar spine, which could be related to the amount of muscle curvatures at each spine level. The curved muscle model generally showed higher compression and lower anterior-posterior and lateral shear loads than the straight-line muscle model. It might be partially related to the muscle paths of the erector spinae (major power producing muscle). In curved muscle model, erector spinae was placed more parallel with the lumbar spine curvature than the straight-line muscle model. It could affect the spinal load distributions such as higher compression and lower shears loads in the curved muscle model compared to the straight-line muscle model. In conclusion, the improved performance of the curved muscle model indicated that the curved muscle approach would be advantageous to estimate precise spinal loads in complex lifting jobs compared to the straight-line muscle approach.